Innovative technologies for critical infrastructure resilience: Impact-informed governance in energy and water sectors - Zherdev, Nikolay; Mateeva, Liliana; Klein, Oliver; Nam, Christine; Bouwer, Laurens; Siegel, Y.; Butler, Jethro; Kimmich, Christian (Crisis Management Days, 2025)
Critical infrastructures (CIs) provide essential public services, including energy and water supply, transport services, and healthcare, which are vital for the functioning of society and the economy (Constantin et al., 2022). Given their strategic importance, CIs are considered (semi)public goods, requiring a comprehensive assessment of their broader societal impacts – both positive (e.g. economic growth, social well-being) and negative (e.g. service disruptions, environmental risks). The increasing integration of innovative technologies in CIs to enhance resilience during crises and normal operations necessitates a systematic approach to impact assessment that considers public benefits and associated costs. Despite the widespread use of impact assessment methodologies to evaluate new technologies in organisations (Yurrita et al, 2022), studies focusing on public interest indicators in the governance of CI remain limited. This study applies an impact assessment framework developed within the SUNRISE project (the SUNRISE project, 2022; Zherdev et al, 2024) to examine how CIs in the energy and water sectors account for socio-economic and environmental effects in their decision-making. Given the significance of externalities – such as ensuring uninterrupted service supply, mitigating climate risks, and sustaining economic stability (Paoli et al, 2010) – the research integrates relevant social, economic, and environmental indicators to assess the implementation of novel technological solutions. The analysis considers the multi-level impacts (micro, regional and national) of CI resilience strategies and evaluates how their operations align with EU and national policies on public service provision. Using policy analysis, qualitative interviews with CI operators, regulators, and experts, as well as survey data, the study identifies key challenges and opportunities in aligning technological innovation with governance frameworks. Findings highlight gaps and misalignments between current CI strategies and regulatory policies, offering evidence-based policy recommendations to enhance resilience and sustainable service provision.